(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This Research seeks to reveal the theory of philosopher Thomas Kuhn in the history of science, where he believes that science does not develop in a gradual cumulative; but a revolutionary separatist through cognitive segments and leaps qualitative "scientific revolutions" in which a guiding model (paradigm) to replace another model, and what produces It is about changing the curricula used and the principles, terms and scientific techniques in circulation. These scientific revolutions occur from the stage of normal science when scientists face complex problems (anomalies - puzzles) that do not accept the scientific explanations prevailing under the existing guiding model in a certain period of time. Scientists then try to reconcile this existing model with abnormal phenomena. When their attempts fail, the crisis phase (the phase of the crisis of science) fails, members of the scientific community try to revise the basic foundations and axioms. As a result, the revolutionary phase of science begins.